Studies on lipase enzyme production by indigenously isolated Bacillus Cereus (BAIT GCT 127002 ) and Bacillus Cereus (BAIT GCT 127001) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Microbial lipases holds a prominent place among biocatalysts that act on carboxylic ester bonds.  This present study involves about eight strains isolated form slaughter house waste water,Coimbatore producing lipase.Among those strains , two bacterial strains exhibiting high lipase production  were identified as  Bacillus Cereus (BAIT GCT 127002 ) and Bacillus Cereus (BAIT GCT 127001 ) by both biochemical analysis and 16S rRNA sequencing.  Initial studies were done for optimizing lipase production using many components such as time course,Carbon sources ,pH and innoculum volume which  revealed maximum lipase acitivity (43.37 U/ml) at 24 hours, using  palm oil , at pH 8 and innoculum volume of 1 ml by Bacillus Cereus (BAIT GCT 127002 ).Further the percentage  removal of oil from oil stained fabric was determined using partially purified lipase with or without detergents and the results indicated 20% ,30% removal with use of  crude lipase and commercial detergent respectively.Hence, lipase from Bacillus Cereus(BAIT GCT 127002 )   can be regarded as an ideal ingredient that can be used in the laundry detergents.